Trends in allogeneic haematopoietic cell transplantation for myelofibrosis in Europe between 1995 and 2018: a CMWP of EBMT retrospective analysis - McLornan, D; Eikema, D J; Czerw, T; Kröger, N; Koster, L; Reinhardt, Hans Christian; Angelucci, E; Robin, M; Bornhäuser, M; Passweg, J; Clark, A; Vydra, J; et al. (Bone marrow transplantation, 2021)
We performed a retrospective assessment of patient- and transplant-specific characteristics and outcomes for 4142 patients undergoing allogeneic haematopoietic cell transplant for myelofibrosis between 1995 and 2018 across 278 centres. Activity increased steadily across the four analysed eras (<2006, 2006-2010, 2011-2014 and 2015-2018). Median recipient age increased over time between the earliest and most recent cohort (49.4 years (range, 20.1-68) versus 59.3 years (range, 18.1-78.1). Increasing number of patients with a Karnofsky performance status <90 underwent transplant over time. Increased utilisation of matched unrelated donors was apparent (<2006, 22.5% versus 2015-18, 45.2%; p < 0.001). Decreased use of myeloablative conditioning, increased use of busulphan-based platforms and anti-thymocyte globulin was evident. Of note, rates of acute (a)GVHD grade II-IV by day +100 decreased over time (p = 0.027) as did rates of chronic (c) GVHD, predominantly extensive cGVHD (<2006, 36% (31-41%) versus 2015-18, 23% (21-25%); p = 0.001). Overall, significant factors associated with worse overall survival and non-relapse mortality (NRM) remained older age, use of donors other than matched sibling, recipient CMV seropositivity and a lower Karnofsky performance status (<90). Multivariable analysis demonstrated improvements in overall survival and reductions in relapse risk over time with stable NRM rates despite increasing numbers of older, less fit patients and use of unrelated donors.
Keywords: transplantace hematopoetických kmenových buněk; Humans; lidé středního věku; Graft vs Host Disease; Hematopoietic Stem Cell Transplantation; Aged; příprava pacienta k transplantaci; dospělí; mladý dospělý; senioři; lidé; Primary Myelofibrosis; primární myelofibróza; Adult; Middle Aged; nemoc štěpu proti hostiteli; Retrospective Studies; Transplantation Conditioning; Young Adult; retrospektivní studie